Software Development Practice as Baradian Entanglement. - Prior, Julia; Leaney, John (Human Organization)
Software development practice is a messy, complicated, and constantly shifting human endeavor. Barad's concept of "entanglement" helps to theorize complex sociotechnical systems. We are testing the application of this theory to understand and explain software development practices, as our work appears to be the only ethnographic research using Barad in any technology industry. Our continual aim is to understand large-scale, collaborative software development more deeply in practice and to discover appropriate theories that describe our observations and insights. Both authors are experienced software engineers and researchers. Through an ongoing longitudinal ethnographic study at a large Australian software development company, we explore, support, and improve the lived experience and practice of the software developers that work there. Ethnographic insights and an appreciation of the mutual constitution of situated phenomena have expanded over several years into an elaboration of entanglement as a more insightful explanation of software development practice. This research is having a significant impact on the participant developers and organization, including changes in measurement practices, mentoring, knowledge management, and innovation.